Effect of continuous nursing intervention on medication safety in elderly patients with chronic diseases (延续性护理对老年慢性病患者用药安全的影响) - WANG Huaxin (王华新); DAI Hui (戴晖); TANG Ling (唐玲); ZHAO Jialu (赵佳璐) (中西医结合护理)
Objective To investigate the effect of continuous nursing intervention on medication safety in elderly patients with chronic diseases. Methods Totally 100 elderly patients with chronic diseases were randomly divided into the observation group and control group, with 100 cases in each group. Patient in the control group received routine discharge guidance and follow-up, and those in the observation group were given continuous nursing intervention. The medication safety and rehospitalization situation were analyzed at 6 month after discharge form hospital. A questionnaire survey was conducted to measure the compliance and satisfaction of patients after discharge form hospital. Results The rates of unauthorized increase, decrease, withdrawal and missing of medication in the observation group were lower than those in the control group(P＜0. 05, respectively). The re-hospitalization rate in the observation group was lower than that in the control group (4. 00% vs. 18. 00%, P＜0. 05). The scores of satisfaction evaluation about dietary, rehabilitation exercise, hospital reexamination and hygiene in the observation group were higher than those in the control group(P＜0. 01). The satisfaction rate in the observation group was higher than those in the control group(P＜0. 05). Conclusion The continuous nursing intervention is potentially effective to improve the medication safety and treatment compliance after discharge from hospital in elderly patients with chronic diseases. (目的 探讨延续性护理对老年慢性病患者用药安全的影响。方法 选取2019年8月—2020年2月治疗后出院的100例老年慢性病患者为研究对象, 采用数字随机表法分为观察组和对照组, 各50例。对照组出院时给予常规出院指导, 观察组实施延续性护理干预。对两组患者出院后6个月的用药安全情况和再住院情况进行统计分析, 运用调查问卷的形式评估两组患者出院后依从性和满意度情况。结果 观察组患者出院后擅自增减药、漏服药、停药的比例低于对照组, 差异有统计学意义(P＜0. 05)。观察组患者的再住院率为4. 00%(2/50), 低于对照组的18. 00%(9/50), 差异有统计学意义(P＜0. 05)。观察组患者出院后在合理饮食、康复锻炼、按时复查、卫生清洁方面的依从性评分高于对照组 (P＜0. 01)。观察组患者护理满意度高于对照组(P＜0. 05)。结论 延续性护理可提高老年慢性病患者出院后用药安全性和依从性, 降低再住院率, 提高护理满意度。)